Fairy Tales and Promotion of Early Childhood Development - Treewong, Pitchayapa (Community and Social Development Journal, 2023)
The purpose of this academic article is to present the selection of storybooks for early childhood children, which must consider the ability to promote the development and imagination of early childhood children, and must consider children of each age who are able to receive knowledge and interests are different, because fairy tales are considered an important helper for parents and teachers in raising early childhood children, because in addition to providing fun, fables also provide knowledge and ideas that include morals and ethics. It is crucial to consider a child's age, interest, perception, and skill when determining whether or not a fairy tale is acceptable for young children. As a result, there is a genuine advantage to children's learning in that they will start to identify tales from seen sights and heard sounds as they gradually come to understand the meaning of the words until they can connect the two. In addition to learning the facts and tales that make the literature interesting to read, memorize them. As a result, selecting tales to help young children develop their skills will also strengthen their relationships with their parents and teachers, who have been telling tales to children since they were still in the womb. Additionally, selecting tales that are age-appropriate will be able to effectively support the development of the kids in all areas.